P‐185: Enhanced Light Extraction of Flexible Organic Light‐emitting Diodes by Ag Nanoparticles as Scattering Layer. Issue 1 (30th May 2018) - Kim, Seonju; Choi, Junhee; Park, Young Wook; Ju, Byeong-Kwon
Abstract : We proposed the fabrication of the light scattering layer by dewetted large Ag nanoparticles at low temperature (∼150oC). Since the larger Ag nanoparticles (AgNPs) induce the strong light scattering while reducing the absorption of AgNPs, the light extraction in organic light emitting diodes can be improved by using large Ag nanoparticles. We demonstrated the improvement of light extraction in flexible organic light emitting didoes by the light scattering of AgNPs